Airborne endotoxin concentrations in indoor and outdoor particulate matter and their predictors in an urban city. (27th February 2017) - Yoda, Y.; Tamura, K.; Shima, M.
Abstract: Endotoxins are an important biological component of particulate matter and have been associated with adverse effects on human health. There have been some recent studies on airborne endotoxin concentrations. We collected fine (PM2.5 ) and coarse (PM10‐2.5 ) particulate matter twice on weekdays and weekends each for 48 hour, inside and outside 55 homes in an urban city in Japan. Endotoxin concentrations in both fractions were measured using the kinetic Limulus Amebocyte Lysate assay. The relationships between endotoxin concentrations and household characteristics were evaluated for each fraction. Both indoor and outdoor endotoxin concentrations were higher in PM2.5 than in PM10‐2.5 . In both PM2.5 and PM10‐2.5, indoor endotoxin concentrations were higher than outdoor concentrations, and the indoor endotoxin concentrations significantly correlated with outdoor concentrations in each fraction ( R 2 =0.458 and 0.198, respectively). Indoor endotoxin concentrations in PM2.5 were significantly higher in homes with tatami or carpet flooring and in homes with pets, and lower in homes that used air purifiers. Indoor endotoxin concentrations in PM10‐2.5 were significantly higher in homes with two or more children and homes with tatami or carpet flooring. These results showed that the indoor endotoxin concentrations were associated with the household characteristics in addition to outdoor endotoxin concentrations.